RESPON VASODILATASI EKSTRAK METANOL DAUN Macaranga lamellata Whitmore SECARA IN VITRO - Amalia, Elfiza; Astuti, Winni; Marliana, Eva (Jurusan Kimia FMIPA UNMUL, 2021)
The research about in vitro vasodilatation response of methanol extract of Macaranga lamellata whitmore leaves was carried out. This research was conducted to determine the vasodilatation response of methanol extract of Macaranga lamellata Whitmore leaves on changes in aortic tone of Wistar rat. The methods used include the in vitro methods by using separated aortic organ of Wistar rat. Methanol extract were given cumulatively in bath organs. Positive control is used methacholine and negative control is used DMSO solvent. T-test statistical was done to determine the significant differences between groups. Phytochemical test results showed that total methanol extract contained alkaloids, polyphenol, steroids, flavonoids and saponins. Percentage change in aortic tone by using methanol extract concentration of 0.3; 1 and 3 mg/mL respectively were -7.422%; -9.641% and -10.593%. Methanol extract of Macaranga lamellata Whitmore leaves have antihypertensive potential. Keywords: Antihypertensive, Aortic, In vitro, Macaranga lamellata Whitmore, Vasodilatation